Efectos de la aplicacion de Biol en forma folear sobre los rendimientos del caupi (Vigna sp), variedad San Roque, región San Martín. - Díaz García, Juan Carlos (2008)
This research was conducted during the period from August 2007 to October 2007 in the Fundo Miraflores of the National University of San Martin, Ahuashiyacu, District Band Shilcayo, Province of San Martin, Department of San sectors Martin; in order to determine the effect of different doses of biol applied in folear form on the cultivation of cowpea variety "san roque ~ and benefit / cost ratio. The factors studied were composed of the cowpea crop variety "San Roque" with different doses of Biol (T1 = 40Lt / ha; T2 = 60lt / ha; T3 = 80lt / ha); T4 = Control Chemical and T5 as absolute Witness .The experimental design was complete block design at random (DBCA), which consisted of 5 treatments and 4 repetitions. The results indicate that the best dose of biol both greater plant height, number of pods per plant, number of seeds per plant, and a higher yield per hectare I got the (T2 = 60lt of biol / ha). Likewise it was observed that the T4 = (chemical control), which is obtained with higher performance 1972,21Kg / ha, even higher than the dose of T2 biol 32, 15Kg more than this. On average, using higher doses of biol (T3 = 80lt of biol / ha), there is a higher cost of production 1711.265 / performance and lower 1786,24Kg relation to the other treatments biol. The cost / benefit ratio, which was obtained greatest benefit (T1 = 40Lt biol / ha) and the lowest profit was (T3 = 80Ltde biol / ha).